Physical Activity vs. Redox Balance in the Brain: Brain Health, Aging and Diseases - Paweł Sutkowy; Alina Woźniak; Celestyna Mila-Kierzenkowska; Karolina Szewczyk-Golec; Roland Wesołowski; Marta Pawłowska; Jarosław Nuszkiewicz (MDPI AG, 2021)
It has been proven that physical exercise improves cognitive function and memory, has an analgesic and antidepressant effect, and delays the aging of the brain and the development of diseases, including neurodegenerative disorders. There are even attempts to use physical activity in the treatment of mental diseases. The course of most diseases is strictly associated with oxidative stress, which can be prevented or alleviated with regular exercise. It has been proven that physical exercise helps to maintain the oxidant-antioxidant balance. In this review, we present the current knowledge on redox balance in the organism and the consequences of its disruption, while focusing mainly on the brain. Furthermore, we discuss the impact of physical activity on aging and brain diseases, and present current recommendations and directions for further research in this area.